The Influence of Organizational Culture and Big Data Analytics on Employee Performance Mediated by Organizational Support at PT XYZ Operating in the Consumer Goods Sales Industry - Christine Febriana Sitorus; Yohana Cahya F. Palupi Meilani (SEAN Institute, 2024)
This study investigates the influence of organizational culture and big data analytics on employee performance, with organizational support as a mediating variable. Conducted at PT XYZ, a company in the essential goods sales industry (including rice, eggs, fruits, and vegetables), the research involved 90 employees using a quantitative approach. Data collection utilized questionnaires with a 5-point Likert scale, and the analysis employed Partial Least Squares Structural Equation Modelling (PLS-SEM) to explore relationships among variables. The results revealed several key insights. First, big data analytics does not significantly organizational support, while organizational culture positively and significantly affects it. Second, organizational support does not significantly impact employee performance, but both big data analytics and organizational culture have direct positive effects on employee performance. Third, mediation testing showed that organizational support does not mediate the relationship between big data analytics and employee performance, nor between organizational culture and employee performance. Based on these findings, it is recommended that PT XYZ prioritize enhancing employee capabilities, particularly among leaders, in communication and collaboration, to better utilize company support, such as systems and big data analytics. Additionally, establishing a strong organizational culture can significantly boost employee performance by fostering a supportive and comfortable work environment. The study highlights the importance of integrating technology and culture to achieve organizational success.